Synthesis and Characterization of Co-Polymer (Styrene / Allyl 2,3,4,6-tetra-O-acetyl-β-D-glucopyranoside) and Studying some of its thermal properties - Yousef Wadouh; Rana Ghenem; Warda Khalil; Mohammad Keshe (مجلة بغداد للعلوم)
In this research, a Co-polymer (Styrene / Allyl-2.3.4.6-tetra-O-acetyl-β-D-glucopyranoside) was synthesized from glucose in four steps using Addition Polymerization according to the radical mechanism using Benzoyl Peroxide (BP) as initiator. Initially, Allyl-2.3.4.6-tetra-O-acetyl-β-D-glucopyranoside monomer was prepared in three steps and the reaction was followed by (HPLC, FT-IR, TLC), in the fourth step the monomer was polymerized with Styrene and the structure was determined by FT-IR and NMR spectroscopy. The reaction conditions (temperature, reaction time, material ratios) were also studied to obtain the highest yield, the relative, specific and reduced viscosity of the prepared polymer was determined, from which the viscosity average molecular weight was calculated, which amounted to about (63,000 g/mol). Thermal properties of the polymer were studied by Differential Scanning Calorimeter (DSC) and determining the Oxidation Induction Time (OIT).